2021
DOI: 10.1088/1755-1315/881/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

The implication of street network design for walkability: A review

Abstract: A street network-friendly design allows walkability among people and is proven beneficial to the environment, community health, and economy of the city. Walkability in a street network increases potential trips by pedestrians through sidewalks and linked streets to create shorter travel distances. Street designs for pedestrian walkways are commonly ignored, with more focus on vehicular access, consequently leading to a lack of effort in improving the street network designs linked to various destinations. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Furthermore, visual elements improve the benefit of soundscape-context affection, whether through visual or auditory stimuli [27]. The city and built environment indicator presented the highest result of 20 articles, which suggested that built environment attributes influenced urban development and provided opportunities for commercial activities in livening the place [28].…”
Section: Effects Of Contextual Characteristic On Visual Perceptionmentioning
confidence: 99%
“…Furthermore, visual elements improve the benefit of soundscape-context affection, whether through visual or auditory stimuli [27]. The city and built environment indicator presented the highest result of 20 articles, which suggested that built environment attributes influenced urban development and provided opportunities for commercial activities in livening the place [28].…”
Section: Effects Of Contextual Characteristic On Visual Perceptionmentioning
confidence: 99%
“…Those features are shown in table 3 as the walkable street indicators. It has 13 indicators to make pedestrians love to walk in their city, such as providing a lively walking environment [45], creating social interaction [46], and the presence of public transport [47]. Most of the indicators are put on the physical and social aspects because they directly impact the pedestrians.…”
Section: Walkable Streetmentioning
confidence: 99%
“…Creating a sustainable space [46] WS2 Providing parking areas [47] Providing a complete street WS3 Cultural elements (high presence of cultural elements or convivial points) [47] The presence of aesthetical elements [47] Environments have full pedestrian facilities [45] Providing many aesthetically pleasing elements [45] Street improvements led to an increase in pedestrian volume and influenced walking experiences [46] Improving pedestrian facilities resulted in improved neighbourhood quality [46] Creating broad green areas with shaded pathways, underground parking, and bicycle lanes [46] A new complete street renovation can attract people's interest [46] Enhancement of current infrastructure for pedestrians [46] The street environment needs to be anthropometrically and ergonomically sensitive [49] Satisfying the individual's basic day-to-day needs by providing many facilities [4] Attractive, lively, and friendly environments [45] Built environment factors influenced decisions to walk for short trips [46] Providing an exercise-inducing environment with many supported features [45] Providing a sensory experience of the street that derives pleasure [50]…”
Section: Comfortable Microclimatic Conditions [48] Ws1mentioning
confidence: 99%
See 2 more Smart Citations